Flexible Magnetic Reading/Writing System: Heat-assisted Magnetic Recording. (2016) - Taptimthong, Piriya; Düsing, Jan Friedrich; Rissing, Lutz; Wurz, Marc Christopher
Abstract: Data storage is one of indispensable technical assets defined in a frame work of Industry 4.0. Among many data storage technologies, inherent magnetic data storage on surfaces of technical components is promising, especially when the components are employed in harsh environments. Comparing with other storage technologies like labels, RFID tags and engraving, the inherent magnetic storage is rewritable and resistant to weathering. High temperature and a high magnetic field, however, can degrade or even delete magnetically stored data. This limitation can be coped with using a medium with higher coercivity that can withstand external magnetic fields and high temperature. As a consequence of higher coercivity, a higher write field is required to magnetize the medium. A design of a flexible write head that is suitable for storage applications on surfaces of technical components, is restricted by head-medium interface criterions, and hence field strength generated from the write head cannot be arbitrary large. To solve this problem, a heat-assisted magnetic recording (HAMR) is proposed as a means to temporarily reduce coercivity of a medium during writing. A realization of a HAMR module and an experiment as well as its positive results are presented in this work.